Advancing the science of microbial symbiosis to support invasive species management: a case study on Phragmites in the Great Lakes - Kowalski, Kurt P.; Bacon, Charles; Bickford, Wesley; Braun, Heather; Clay, Keith; Leduc-Lapierre, Michèle; Lillard, Elizabeth; McCormick, Melissa K.; Nelson, Eric; Torres, Monica; White, James; Wilcox, Douglas A. (Frontiers in Microbiology, 2015)
A growing body of literature supports microbial symbiosis as a foundational principle for the competitive success of invasive plant species. Further exploration of the relationships between invasive species and their associated microbiomes, as well as the interactions with the microbiomes of native species, can lead to key new insights into invasive success and potentially new and effective control approaches. In this manuscript, we review microbial relationships with plants, outline steps necessary to develop invasive species control strategies that are based on those relationships, and use the invasive plant species Phragmites australis (common reed) as an example of how development of microbial-based control strategies can be enhanced using a collective impact approach. The proposed science agenda, developed by the Collaborative for Microbial Symbiosis and Phragmites Management, contains a foundation of sequential steps and mutually-reinforcing tasks to guide the development of microbial-based control strategies for Phragmites and other invasive species. Just as the science of plant-microbial symbiosis can be transferred for use in other invasive species, so too can the model of collective impact be applied to other avenues of research and management.